Effect of Cold Rolling Process on Mechanical, Corrosion and Hydride Orientation Properties in Zr-1%Nb Alloys - M Dadfar; M Ansaripour (مجله علوم و فنون هسته‌ای, 2013)
A radially-oriented hydride (RH) has been known to deteriorate the final properties of fuel claddings. One of the most effective factors on formation of these hydrides is cold working process. In this work, we were concerned with two different rolling processes to find their effects on mechanical and corrosion properties, as well as, on the hydride orientation of the final tubes. The first process used was our conventional method with six different rolling passes and the other was just involved with four passes. All the microscopic, hydride orientation, mechanical and corrosion behaviors of two samples were examined. The experimental practices showed better results of newly designed cold working process in comparison with our conventional method.